Preliminary study on parking control system for proposed transit oriented development (TOD) area: implementation potential in Petaling Jaya City Council (MBPJ), Malaysia - Ibrahim, N.I.; Adji, B.M.; Karim, M.R. (2011)
Rapid growth in the urbanised area presents many transportation and land use challenges for local and regional policy makers. As part of the key role in land use accessibility, parking management system is of significant importance to travelers making their travel decisions. It affects such diverse travel decisions as mode choice, trip destination choice and trip frequency. Transit Oriented Development (TOD) which offers a mix development of residential, retail, office and open space can respond to these challenges by supporting transit use. The combination of local pedestrian environment with access to CBD by transit would reduce the number of private vehicle dependency that will promote more environmentally friendly and sociable lifestyles. This study tries to look into the potential of parking control system in restricting the use of private vehicle within the proposed TOD area in Petaling Jaya City Council (MBPJ), Selangor, Malaysia.